Neoliberalism and the Irish welfare state : public private partnerships in the delivery of schools and social-housing regeneration - Hearne, Rory (Trinity College (Dublin, Ireland). Department of Geography, 2009)
This project examines the policy background and decision-making process that led to the introduction of Public Private Partnerships (PPPs) in the delivery of public services and infrastructure in Ireland. It draws on geopolitical-economy approaches to explore the role of PPPs in the ongoing processes of the neoliberal transformation of the Irish welfare state. The research addresses the manner in which the development and outcomes and rationales of PPPs in Ireland reflect international experiences.
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin